Kazakh autonomy in China: past and present - Mukametkhanuly, Н.; Massimkhanuly, Д. (Journal of Oriental Studies, 2024)
The PRC is a multinational United State. Applies a policy of regional autonomy to nations within the country. Kazakh Autonomous Regions in China – Ili Kazakh Autonomous Region, Barkol Kazakh Autonomous Region, Mori Kazakh Autonomous Region and Aksai Kazakh Autonomous Regions in Gansu province. This year (2024) marks the 70th anniversary of their creation. The article discusses in detail the formation of bodies in regions densely populated by Kazakhs in China, the implementation of the policy of autonomy and the social development of Kazakhs and today's issues. The purpose of the proposed article is to review the history of the Kazakhs in the Kazakh Autonomous Regions in China, to identify current problems and future challenges. The basic principles of China's policy applied to ethnic minorities are included in the “General program”, the “Constitution of the PRC” and the “Law of regional autonamy of peoples of the PRC”. On the basis of these laws, the social situation of Kazakhs in comparison has improved, the level of Education, Science and culture, the political role and place in Chinese society has increased. However, in recent years, the policy of autonomy in China has not been implemented at the proper level, the rights and interests of ethnic minorities established by the laws of the PRC have been severely violated, and the rights of a small number of nationalities to receive education in their native language have been limited. It is impossible to hide the fact that this situation threatens the preservation of the culture of a small number of nations, especially the Kazakh culture and national identity. Key words: National autonomous territory, Kazakh autonomy in China, autonomy policy, social development, raising the level of education and culture, challenges.